Distinct Function of Estrogen Receptors in the Rodent Anterior Cingulate Cortex in Pain-related Aversion. (July 2020) - Zang, Kai-Kai; Xiao, Xiao; Chen, Li-Qiang; Yang, Yan; Cao, Qi-Lai; Tang, Yu-Long; Lv, Su-Su; Cao, Hong; Zhang, Ling; Zhang, Yu-Qiu
Abstract : Background: Brain-derived estrogen is implicated in pain-related aversion; however, which estrogen receptors mediate this effect remains unclear. This study hypothesized that the different estrogen receptors in the rostral anterior cingulate cortex play distinct roles in pain-related aversion. Methods: Formalin-induced conditioned place avoidance and place escape/avoidance paradigms were used to evaluate pain-related aversion in rodents. Immunohistochemistry and Western blotting were used to detect estrogen receptor expression. Patch-clamp recordings were used to examine N -methyl-D-aspartate–mediated excitatory postsynaptic currents in rostral anterior cingulate cortex slices. Results: The administration of the estrogen receptor-β antagonist 4-(2-phenyl-5, 7-bis [trifluoromethyl] pyrazolo [1, 5-a] pyrimidin-3-yl) phenol (PHTPP) or the G protein–coupled estrogen receptor-1 antagonist (3aS*, 4R*, 9bR*)-4-(6-bromo-1, 3-benzodioxol-5-yl)-3a, 4, 5, 9b-3H-cyclopenta [c] quinolone (G15) but not the estrogen receptor-α antagonist 1, 3-bis (4-hydroxyphenyl)-4-methyl-5-[4-(2-piperidinylethoxy) phenol]-1H-pyrazole dihydrochloride (MPP) into the rostral anterior cingulate cortex blocked pain-related aversion in rats (avoidance score, mean ± SD: 1, 3-bis [4-hydroxyphenyl]-4-methyl-5-(4-[2-piperidinylethoxy] phenol)-1H-pyrazole dihydrochloride (MPP): 47.0 ± 18.9%, 4-(2-phenyl-5, 7-bis [trifluoromethyl] pyrazolo [1, 5-a] pyrimidin-3-yl) phenol (PHTPP): −7.4 ± 20.6%, and [3aS*, 4R*, 9bR*]-4-[6-bromo-1, 3-benzodioxol-5-yl]-3a, 4, 5, 9b-3H-cyclopenta [c] quinolone (G15): −4.6 ± 17.0% vs. vehicle: 46.5 ± 12.2%; n = 7 to 9; P < 0.0001). Consistently, estrogen receptor-β knockdown but not estrogen receptor-α knockdown by short-hairpin RNA also inhibited pain-related aversion in mice (avoidance score, mean ± SD: estrogen receptor-α–short-hairpin RNA: 26.0 ± 7.1% and estrogen receptor-β–short-hairpin RNA: 6.3 ± 13.4% vs. control short-hairpin RNA: 29.1 ± 9.1%; n = 7 to 10; P < 0.0001). Furthermore, the direct administration of the estrogen receptor-β agonist 2, 3-bis (4-hydroxyphenyl)-propionitrile (DPN) or the G protein–coupled estrogen receptor-1 agonist (±)-1-([3aR*, 4S*, 9bS*]-4-(6-bromo-1, 3-benzodioxol-5-yl)-3a, 4, 5, 9b-tetrahydro-3H-cyclopenta [c]quinolin-8-yl)-ethanone (G1) into the rostral anterior cingulate cortex resulted in conditioned place avoidance (avoidance score, mean ± SD: 2, 3-bis (4-hydroxyphenyl)-propionitrile (DPN): 35.3 ± 9.5% and (±)-1-([3aR*, 4S*, 9bS*]-4-(6-bromo-1, 3-benzodioxol-5-yl)-3a, 4, 5, 9b-tetrahydro-3H-cyclopenta [c]quinolin-8-yl)-ethanone (G1): 43.5 ± 22.8% vs. vehicle: 0.3 ± 14.9%; n = 8; P < 0.0001) but did not affect mechanical or thermal sensitivity. The activation of the estrogen receptor-β/protein kinase A or G protein–coupled estrogen receptor-1/protein kinase B pathway elicited the long-term potentiation of N -methyl-D-aspartate–mediated excitatory postsynaptic currents. Conclusions: These findings indicate that estrogen receptor-β and G protein–coupled estrogen receptor-1 but not estrogen receptor-α in the rostral anterior cingulate cortex contribute to pain-related aversion by modulating N -methyl-D-aspartate receptor–mediated excitatory synaptic transmission. Abstract : Blockade of the estrogen receptor-β but not the estrogen receptor-α reduced pain-related aversion in rats, a model of the affective components of pain. Administration of an estrogen receptor-β agonist to the rostral anterior cingulate cortex caused conditioned place aversion without altering mechanical or thermal sensitivity. Estrogen receptor-β may be a key receptor controlling the affective components of pain-related behaviors in laboratory models.Supplemental Digital Content is available in the text.